PENGARUH PENGHARGAAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. BTPN SYARIAH (PERSERO) SURABAYA - Riska Ayu Pramesthi; Dian Amorina S (Relawan Jurnal Indonesia, 2020)
This study aims (1) to determine the effect of rewards, motivation and work discipline partially influence employee performance (2) to determine the effect of rewards, motivation and work discipline simultaneously affect employee performance (3) to find out among the variables of appreciation, motivation and work discipline is the most dominant influence on employee performance. The method used in this research is quantitative method. The results of this study are the multiple linear regression equation Y = 2.885E-16 + 0.279 X1 + 0.217 X2 + 0.380 X3 + e. Partially, the award has a significant positive effect with a tcount of 2.093> ttable of 2.004, motivation has a significant positive effect with a tcount of 2.140> ttable of 2.004 and work discipline has a significant positive effect with a ttest value of 2.896> ttable of 2.004. Simultaneously motivation, competency and work discipline affect the performance of the State Civil Apparatus with a Fcount of 19.753> Ftable 2.77. The most influential dominant variable in this study is work discipline with a value of tcount of 2.896